Comparative analysis of wireless communication technologies with application in industrial networks for the Internet of things - Angelov, Krasen (Yearbook Telecommunications, 2024)
The integration of the Internet of Things (IoT) into industrial communication networks is set to become the cornerstone of the communication infrastructure of future smart factories. These factories will comprise digitalized flexible production with a dynamic technological operational schedule and multiple mobile participants. The Internet of Things facilitates the collection of data at the point of use through the utilization of smart devices, which subsequently transmits the gathered information to the enterprise management system for the purpose of decision-making. The foundation for such production lies in the establishment of reliable and secure communication networks, encompassing wireless technologies. The primary contribution of the article is the proposed comparative analysis of the capabilities of modern advanced generations of wireless technologies for wireless data transmission in industrial networks of the Internet of Things, and their applicability for various scenarios. This paper focuses on three particular technologies: 5G (for cellular communication), WLAN (IEEE 802.11ax), and LoRaWAN.